2017
DOI: 10.1089/pho.2016.4258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Three Different Lasers on Eradication ofEnterococcus faecalisandCandida albicansBiofilms in Root Canal System

Abstract: Er,Cr:YSGG laser was the most efficient tool in eradication of E. faecalis and C. albicans biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…Our findings fit with the observation of Kasic et al 27 who reported a 10,000-fold reduction of C. albicans in the presence of E. faecalis using Er:YAG laser irradiation of NaCl inside root canals. The authors did not explain their findings, but it can be speculated that mixing these two strains might lead to different growth and dynamics of the biofilm or to different susceptibility to fluid dynamics.…”
Section: Endodontic Disinfection With Er:yag Laser Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings fit with the observation of Kasic et al 27 who reported a 10,000-fold reduction of C. albicans in the presence of E. faecalis using Er:YAG laser irradiation of NaCl inside root canals. The authors did not explain their findings, but it can be speculated that mixing these two strains might lead to different growth and dynamics of the biofilm or to different susceptibility to fluid dynamics.…”
Section: Endodontic Disinfection With Er:yag Laser Discussionsupporting
confidence: 93%
“…This is in line with Sahar-Helft et al 25 who reported that Er:YAG LAI did not improve CFUs of E. faecalis biofilm compared with manual dynamic irrigation, and also Ordinola-Zapata et al 26 reported better antibacterial effects on E. faecalis with the use of needle irrigation of NaOCl than the use of LAI. The same was reported by Kasic et al, 27 who found a significant but clinically irrelevant 10% reduction of E. faecalis counts in artificially infected root canals. However, it was reported that, using SEM analysis as validation method, Er:YAG irradiation of NaCl solution inside the root canal was able to partially remove the E. faecalis biofilm from root canal walls and to expose dentinal tubules.…”
Section: Endodontic Disinfection With Er:yag Laser Discussionsupporting
confidence: 85%
“…The results were tested and compared to CSI, [42][43][44] diode laser irradiation, 45 PUI, 44 UAI, 46 and Er,Cr:YSGG LAI. 47 One study varied the laser settings and NaOCl concentration and concluded that the decontamination was only efficient with 5% NaOCl and no irrigation protocol other than PIPS (Table 2). 48 Smear Layer Removal Seventeen studies were included in the analysis of smear layer removal.…”
Section: Debris Removalmentioning
confidence: 99%
“…aPDT is two stage process, this involves delivery of photosensitizer dye at first stage and then application of laser light, this produces a toxic photochemistry, leading to microbial destruction [45,46,47]. Successful eradication of various clinically relevant microbes notably S. mutans and E. faecalis have been reported using aPDT approach, with effective destruction of 97-99.9% of planktonic bacterial loads [48,49].…”
Section: Apdt In Endodonticsmentioning
confidence: 99%